2019
DOI: 10.5937/skolbiz2-22612
|View full text |Cite
|
Sign up to set email alerts
|

Research on the relationship between intellectual capital and indicators of work results of employees in the banking sector of the Republic of Serbia

Abstract: Intellectual capital in the knowledge economy is recognized as a key driver of value creation in the banking sector, which affects the business results of banks and the success of realization of business activities. The efficiency of the use of intellectual capital depends on the employees, which points out the need to analyse the relationship between intellectual capital and the efficiency of employees. The aim of the research in this paper is to identify the relationship between intellectual capital and indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 18 publications
1
6
1
Order By: Relevance
“…Research results show that IC is a significant factor of the high productivity of hotel managers. The relationship between IC and employees' productivity was also confirmed by Huang and Jim Wu (2010); Bontis et al (2015); Kengatharan (2019); Ognjanović and Pešterac, 2019;Weqar et al (2020); Xu and Li (2021). The results of the study are in agreement with the previous conclusions that employees are an important component of productivity and activity in the hotel (Rahimpour et al, 2020).…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…Research results show that IC is a significant factor of the high productivity of hotel managers. The relationship between IC and employees' productivity was also confirmed by Huang and Jim Wu (2010); Bontis et al (2015); Kengatharan (2019); Ognjanović and Pešterac, 2019;Weqar et al (2020); Xu and Li (2021). The results of the study are in agreement with the previous conclusions that employees are an important component of productivity and activity in the hotel (Rahimpour et al, 2020).…”
Section: Discussionsupporting
confidence: 88%
“…Some previous studies have not found a direct link between productivity and components of IC (Ghosh & Mondal, 2009;Pal & Soriya, 2012). Ognjanović and Pešterac (2019) conclude that IC does not affect the value-added per employee in the Serbian banking sector.…”
Section: Relationship Between Intellectual Capital and Employee Produ...contrasting
confidence: 51%
See 3 more Smart Citations